Unusual Sperm Morphology in Two Sedentary Songbird Species - Emily R. A. Cramer; Gaute Grønstøl; Phred M. Benham; Carla Cicero; Rauri C. K. Bowie; Daniel J. Tobiansky; Jan T. Lifjeld (Ecology and Evolution)
ABSTRACT Sperm morphology can differ dramatically among closely related species. Within songbirds, the typical filiform sperm has a slender, corkscrew‐shaped head and an elongated midpiece coiled around the flagellum. However, three songbird species are known to have an unusual tadpole‐like sperm morphology with a round or ellipsoid head and short, uncoiled midpiece, which may arise developmentally via neoteny. Here, we describe tadpole‐like sperm phenotypes from two additional songbird species, the white‐breasted nuthatch (Sitta carolinensis) and the wrentit (Chamaea fasciata). These five species with tadpole‐like sperm share several ecological characteristics that can inform hypotheses for the evolution of this unusual phenotype: They are largely non‐migratory, form long‐lasting pair bonds, and have high paternal investment, small testes (no data for wrentit), and short and highly variable sperm lengths. These characteristics could indicate particular natural selection pressures driving physiological states such as low testicular testosterone levels. Additionally, though direct measures of female promiscuity are lacking in these species, these characteristics are consistent with weak post‐copulatory sexual selection. Further study of these similar yet independent evolutionary events, across all levels of analysis, would be valuable for understanding how such dramatic shifts in phenotype evolve.